ANALYSIS OF THE DEVELOPMENT POTENTIAL OF THEMATIC CREATIVE ECONOMY SECTORS TO SUPPORT ECONOMIC GROWTH AND COMMUNITY WELFARE IN SURAKARTA CITY - Herwiyanto; Inna Nur Rokhmah; Aziz Baizuri; Iin Emy Prastiwi; Nahla Uyuni Salsabila (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study explore the development potential of thematic creative economy sectors in Surakarta, including batik, handicrafts, culinary products, and design, to support economic growth and enhance community welfare. The research is motivated by the transition from a resource-based economy to one driven by creativity, innovation, and knowledge. As a city with a strong cultural identity and rich artistic heritage, Surakarta has significant opportunities to strengthen the competitiveness of its creative industries. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The data were analyzed using descriptive analysis, SWOT analysis, and the Analytical Hierarchy Process (AHP) to identify development priorities and formulate strategic recommendations. The study examines the characteristics and potential of creative economy subsectors, identifies challenges in developing thematic creative economy zones, and proposes an integrated and sustainable development framework. The findings provide insights for policymakers and stakeholders in designing effective development strategies. These strategies are expected to enhance regional competitiveness, strengthen local cultural identity, create employment opportunities, and promote inclusive and sustainable economic development in Surakarta.